Effects of color fading ozonation on the color yield of reactive-dyed cotton. (May 2019) - He, Zhenglei; Li, Mengru; Zuo, Danying; Xu, Jie; Yi, Changhai
Abstract: Ozonation is increasingly used for color fading dyed textile nowadays. This paper studied the overall effect of color fading ozonation on the color yield of cottons dyed by Reactive Blue FL-RN (RB-RN), Reactive Red FL-2BL (RB-2BL) and Reactive Yellow FL-2RN (RY-2RN) respectively. In which, the color fading effects in terms of reflectance curves, L*a*b* values and the kinetic studies regarding K/S values are investigated. Experimental analysis has been carried out for finding the effects of pH, temperature and water pick-up on the ozonation process. It is found that color fading ozonation has stable performance in the respects of lightness and color difference on treated cottons, and the decolorization reactions in ozonation are assumed as pseudo secondary order (for cottons dyed by RB-RN and RY-2RN) and pseudo third order (for cottons dyed by RR-2BL) respectively. It is also found that alkaline as pH in the range of 7–10 and higher temperature range from 40 to 80 °C are suggested along with a water pick-up around 75% to promote the color fading efficiency in color fading with respect to the dyes in this study.